2022
DOI: 10.2147/nss.s351274
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Sleep Parameters and Sleep Staging (Slow Wave Sleep) in Athletes by Fitbit Alta HR, a Consumer Sleep Tracking Device

Abstract: Purpose Sleep is an essential factor for athletes, and it is important to intervene in sleep to manage it. We need a device that can evaluate sleep easily and constantly. Consumer wearable devices can be useful tools for athletes. In order to use consumer wearable devices in clinical research, it is essential to conduct a validation study. Thus, we conducted a validation study to assess the Fitbit Alta HR TM (FBA)- a consumer wearable device with an accelerometer and a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Finally, the top feature associated with sleep was the average length of deep sleep. A comparison of Fitbit’s deep sleep stage with EEG signals found that it aligns with the N3 stage of the NREM sleep stage [ 54 ]. There is interest around the role of N3 sleep in dementia given its pivotal role in memory consolidation, but evidence about this association is still limited [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the top feature associated with sleep was the average length of deep sleep. A comparison of Fitbit’s deep sleep stage with EEG signals found that it aligns with the N3 stage of the NREM sleep stage [ 54 ]. There is interest around the role of N3 sleep in dementia given its pivotal role in memory consolidation, but evidence about this association is still limited [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a rapid growth trend may occur. 33 Fitbit devices can measure not only sleep, but also heart rate and physical activity. The validity of various Fitbit device models was evaluated through meta-analysis and discovered as an important factor of validity events in heart rate function and physical activity measurement function.…”
Section: Discussionmentioning
confidence: 99%
“… 4 Contrary to actigraphy-only devices, multi-sensor devices allow for the predictionof sleep stages above and beyond simple binary sleep/wake distinctions. 7 …”
Section: The Goodmentioning
confidence: 99%